A systematic review and three-level meta-analysis of the effects of stroboscopic training on sport-specific performance - Wang, Y.; Wang, Q.; Bao, H.; Dong, X.; Cai, K.; Chen, A. (Journal of Sports Sciences, 2026)
Against the backdrop of pursuing optimal athletic performance, researchers are exploring safe, side-effect-free interventions. This study systematically evaluated the effects of Stroboscopic Visual Training (SVT) on sport-specific performance and examined potential moderating effects of intervention parameters and individual characteristics. Following PRISMA guidelines, a systematic search was conducted and studies screened using PICOS criteria. Thirteen studies were included, yielding 30 effect sizes. A three-level meta-analysis revealed a small-to-moderate positive effect of SVT on sport-specific performance (Hedges` g = 0.35, 95% CI: 0.12-0.58, p < 0.01). Moderator analyses showed that intervention frequency significantly predicted outcomes (p = 0.03), whereas age, training experience, and duration did not. Sensitivity analyses confirmed robustness of findings. Risk of bias was moderate (ROB 2), and evidence quality was graded "moderate" (GRADE). SVT appears to be a safe, practical training tool that enhances sport-specific performance. However, methodological heterogeneity and limited sample representativeness highlight the need for further high-quality randomized controlled trials to confirm the stability and generalizability of these effects.